Characterization of Cu/PAr/CdS MIS structure for sensor applications - Caliskan, M.; Kuruoglu, F.; Serin, M. (NATL INST OPTOELECTRONICS, 2014)
In this study, electrical characterization of. the Cu/PAr/CdS MIS structures were made for sensor application. The main electrical parameters of MIS structure such as the ideality factor (n), barrier height (phi(B)), series resistances (Rs) and interface state density (Nss) were determined at various environments. The series resistance of structures was found 696 Omega and 818 Omega respectively at atmosphere and chloroform environments. It is observed the structure is suitable for sensor applications. Examination of gas sensing property of diode, I-V measurements were done in chloroform atmosphere and constant voltage measurements were done at different gas atmosphere. With the exposure of chloroform, the resistance of diode increases and with discontinuation of gas flow, diode was reverted back to its initial. Therefore, it was understood that the diode was suitable for the sensor applications.
Keywords: Schottky junction; CdS; PAr; Gas sensor; FIELD-EFFECT TRANSISTOR; POLYANILINE THIN-FILMS; CONDUCTING POLYMER; HUMIDITY SENSOR; GAS SENSORS; SEMICONDUCTOR; PRESSURE; POLYPYRROLE; JUNCTION; ACID; Materials Science; Optics